Steel-concrete composite bridges designing with Eurocodes - Collings, David (ICE publishing, 2013)
The second edition of the bestselling Steel-concrete Composite Bridges is fully up-to-date with the methods now used for these structures in accordance with Eurocodes introduced since publication of the first edition